TRAF2 phosphorylation promotes NF-κB–dependent gene expression and inhibits oxidative stress-induced cell death - Zhang, Laiqun (The American Society for Cell Biology, 2011)
Tumor necrosis factor α (TNF-α) receptor–associated factor 2 (TRAF2) regulates activation of the c-Jun N-terminal kinase (JNK)/c-Jun and the inhibitor of κB kinase (IKK)/nuclear factor κB (NF-κB) signaling cascades in response to TNF-α stimulation. Gene knockout studies have revealed that TRAF2 inhibits TNF-α–induced cell death but promotes oxidative stress–induced apoptosis. Here we report that TNF-α and oxidative stress both induce TRAF2 phosphorylation at serines 11 and 55 and that this dual phosphorylation promotes the prolonged phase of IKK activation while inhibiting the prolonged phase of JNK activation. Prolonged IKK activation trigged by TNF-α plays an essential role in efficient expression of a subset of NF-κB target genes but has no substantial role in TNF-α–induced cell death. On the other hand, TRAF2 phosphorylation in response to oxidative stress significantly promotes cell survival by inducing prolonged IKK activation and by inhibiting the prolonged phase of JNK activation. Notably, stable expression of phospho-null mutant TRAF2 in cancer cells leads to an increase in the basal and inducible JNK activation and B-cell lymphoma 2 (Bcl-2) phosphorylation. In addition, exposure of cells expressing phospho-null mutant TRAF2 to sublethal oxidative stress results in a rapid degradation of Bcl-2 and cellular inhibitor of apoptosis 1 as well as significantly increased cell death. These results suggest that TRAF2 phosphorylation is essential for cell survival under conditions of oxidative stress.